SPECIES STRUCTURE AND GEOGRAPHICAL DISTRIBUTION OF GROUND BEETLES OF GENUS BEMBIDION OF DAGHESTAN REPUBLIC. - G. M. ABDURAKHMANOV; G. M. NAKHIBASHEVA; S. M. KLYCHEVA; S. T. MAGOMEDOVA; Z. M. E. (Юг России: экология, развитие, 2015)
The species structure of Bembidion ground beetles of Daghestan is studies in the work 86 species of 31 subgenus are revealed.